Prevalence of orofacial pain attributed to temporomandibular dysfunction in professional dancers from Curitiba - Oliveira, Milena Novelli de; Kuczera , Milena Sampaio; Geminiani , Júlia Silva; Ravazzi , Glória; Humming , Wagner; Goncalves , Flávio Magno; Stechman-Neto , José (Headache Medicine, 2024)
Introduction: Orofacial pain is a debilitating condition that can often be associated with temporomandibular dysfunction (TMD), a disorder affecting the temporomandibular joint and the masticatory muscles. Professional dancers, due to intense physical demands, poor posture, and stress, may be particularly susceptible to developing TMD and consequently orofacial pain. This study aims to investigate the prevalence of orofacial pain attributed to TMD in professional dancers from Curitiba, with the goal of identifying the need for preventive and therapeutic interventions. Methods: This cross-sectional study analyzed 44 professional dancers, all with more than two years of professional experience, from three renowned ballet schools in Curitiba, PR. Data were collected through structured interviews and clinical examinations using the DC/TMD. Additionally, postural habits, injury history, and stress levels of the dancers were assessed to identify potential risk factors associated with TMD. Results: The average age of the dancers was 27.7 years, with an age range from 18 to 42 years. Of the 44 dancers evaluated, 72.2% (32 dancers) reported at least some sign and symptom of orofacial pain, manifesting primarily as tension headaches, pain in the masseter and temporal muscles, and difficulty chewing. A correlation was also observed between orofacial pain and poor postural habits, as well as high stress levels among the dancers. Conclusion: The high prevalence of orofacial pain among professional dancers in Curitiba suggests a strong association with temporomandibular dysfunction. These findings highlight the need for the implementation of prevention and treatment programs targeted at this specific group of professionals. Interventions such as physiotherapy, postural adjustments, relaxation techniques, and specialized dental follow-up may be effective in reducing the incidence of orofacial pain and improving the quality of life and professional performance of dancers.